The war nurse : a novel - Wood, Tracey Enerson (Sourcebooks Landmark, 2021)
"Superintendent of Nurses Julia Stimson and sixty-five inexperienced young nurses arrive on the front lines of WWI to find chaos. With 1,300 soldiers stuffed into a facility built for 500, providing even the most basic care is challenging-and Julia quickly learns that male doctors see her as a threat to their authority. Based on a true story, The War Nurse follows Julia through WWI in France, while the 1918 Spanish flu pandemic overwhelms medical resources. Julia must confront an unthinkable choice-to challenge her profession and risk her hard-won career, or to let the people she loves die in her arms"--